Framing the Cypriot economic crisis: In the service of the neoliberal vision - Doudaki, Vaia; Boubouka, Angeliki; Tzalavras, Christos (My University, 2019)
This study examines the framing of the bailout-related news in Cyprus, adopting a critical analytical perspective. The examination of the actors’ associations with the main framing components (actors, causes, solutions and effects), as presented in the Cypriot elite press, revealed the dependency, the (non)liability and the economistic frame. These frames reproduce the hegemonic neoliberal discourse over the crisis, while disconnecting the responsibility for the crisis from the agents involved, protecting, thus, the legitimacy of their actions and of their authority. The media studied advocate the implementation of neoliberal policies (expressed in harsh austerity and protection of the banking system), legitimating them as the optimal model not only of the economy, but also of politics and social practice.
Keywords: Bailout; Cyprus; Economic crisis; Frames; Haircut; Negemonic discourse; Neoliberalism; News; News framing